2‐arachidonoylglycerol reduces chondroitin sulphate proteoglycan production by astrocytes and enhances oligodendrocyte differentiation under inhibitory conditions. Issue 6 (2nd January 2020) - Feliu, Ana; Mestre, Leyre; Carrillo‐Salinas, Francisco J.; Yong, V. Wee; Mecha, Miriam; Guaza, Carmen
Abstract: The failure to remyelinate and regenerate is a critical impediment to recovery in multiple sclerosis (MS), resulting in severe dysfunction and disability. The chondroitin sulfate proteoglycans (CSPGs) that accumulate in MS lesions are thought to be linked to the failure to regenerate, impeding oligodendrocyte precursor cell (OPC) differentiation and neuronal growth. The potential of endocannabinoids to influence MS progression may reflect their capacity to enhance repair processes. Here, we investigated how 2‐arachidonoylglycerol (2‐AG) may affect the production of the CSPGs neurocan and brevican by astrocytes in culture. In addition, we studied whether 2‐AG promotes oligodendrocyte differentiation under inhibitory conditions in vitro. Following treatment with 2‐AG or by enhancing its endogenous tone through the use of inhibitors of its hydrolytic enzymes, CSPG production by rat and human TGF‐β1 stimulated astrocytes was reduced. These effects of 2‐AG might reflect its influence on TGF‐β1/SMAD pathway, signaling that is involved in CSPG upregulation. The matrix generated from 2‐AG‐treated astrocytes is less inhibitory to oligodendrocyte differentiation and significantly, 2‐AG administration directly promotes the differentiation of rat and human oligodendrocytes cultured under inhibitory conditions. Overall, the data obtained favor targeting the endocannabinoid system to neutralize CSPG accumulation and to enhance oligodendrocyte differentiation. Abstract : 2‐AG treatment dampens neurocan and brevican production in astrocyte cultures, generating a less inhibitory matrix for oligodendrocyte differentiation. The reduction in neurocan production by 2‐AG involves the CB2 signaling system. 2‐AG promotes oligodendrocyte differentiation under inhibitory conditions.